Pengaruh Celebrity Endorsement dan Brand Trust serta Brand Awareness Terhadap Keputusan Pembelian Skincare Skintific di Kota Samarinda - Adelia Nur Adzki; Heni Rahayu Rahmawati (Ekopedia: Jurnal Ilmiah Ekonomi, 2026)
The purpose of this study was to determine the influence of celebrity endorsement, brand trust, and brand awareness on purchasing decisions for skincare products in Samarinda. This study employed a quantitative approach. The population was skincare product users. Purposive sampling was employed. Based on the existing criteria, 128 respondents met the sample criteria. The data source used in this study was primary data obtained through questionnaires. The data analysis technique used was multiple linear regression analysis using SPSS 26. The results of the study simultaneously showed that celebrity endorsement, brand trust, and brand awareness simultaneously influenced purchasing decisions. The partial results showed that celebrity endorsement and brand trust did not influence purchasing decisions, while brand awareness did influence purchasing decisions